Brain-drain in Ghana's health sector - OWUSU-ANSAH, Joseph (KDI School, 2015)
Two Hundred and Twenty medical doctors and Two Hundred and Twenty Nurses from the Korle-Bu Teaching Hospital, the 37 Military Hospital and the Ridge Hospital, all in Accra, Ghana were sampled using simple random sampling to examine why medical doctors and nurses emigrate to developed countries. Cross-Tabulation was used to analyze two of the three hypothesis of structured questionnaire filled by participants. The effect of the age of young-aged medical doctors (approximately 41.82%) on emigration was not significant from the effect of the age of old-aged medical doctors (approximately 55.46%) on emigration. The effect of the age of young-aged nurses (approximately 41%) on emigration was not statistically significant from the effect of the age of old-aged nurses (approximately 45%) on emigration. The effect of shortperiod medical practice did not statistically differ significantly from the effect of long-period medical practice. The effect of short-period nursing practice did not also statistically differ significantly from the effect of long-period nursing practice. The effect the overall satisfaction of medical doctors on their interest in emigrating was statistically found to be significant. The effect the overall satisfaction of nurses on their interest in emigrating was also statistically found to be significant. Motivation for achievement by medical doctors and nurses was found to be significant. It was concluded that providing medical doctors and nurses with achievement incentives alongside salaries would reduce their emigration to developed countries.
Thesis(Master) --KDI School:Master of Public Policy,2015